(untitled) (Journal of Hama University, 2019)
The aim of this study is to evaluate the effect of some hormonal treatments in estrous synchronization and pregnancy rates and its effect as an alternative method to the traditional method (IntraVaginal Sponges) in shami Goats. In this experiment, 21 Shami goats are used. The females are randomly assigned to three groups (n=7): The first group (Control) is treated with intravaginal sponges containing Medroxy Progesterone Acetates (MPA) for 11 days along with the injection of Cloprostenol (PGF2α) 48 hours prior sponges’ withdrawal. Immediately after sponge removal, (equine Chorionic Gonadotropin) eCG is injected. The second group (GP) is treated with (Gonadotropins Releasing Hormone) GnRH in (day 0) then Cloprostenol in (day 5) . The third group (Ov-synch) is treated using GnRH as injection in (day 0), then with Cloprostenol (day 7) and then GnRH in (day 9). The estrous is monitored and recorded after 24 hours after each treatment. The results show that estrous rates are (100%-85,71%-71,42%) respectively, and the pregnancy rates in the three groups are (85,71%-100%-40%) respectively. The results show significant differences (P< 0.05) in the estrous rates between the control group and the GPG group, and it is also observed that there are significant differences (P< 0.05) in the pregnancy rates between the control group and the GPG, and between the GPG group and GP group. It can be concluded from The study that we can use the GP program as an alternative way to the intravaginal to facilitate reproductive management , save time and effort and improve fertility .